Corbynism : a critical approach - Bolton, Matt (SocietyNow, 2018)
10pm, 8th June 2017: exit polls at the British General Election show Jeremy Corbyn's Labour Party denying the Conservative Party what was widely expected to be a guaranteed increased majority. Crowned Labour leader two years earlier, the British political class were convinced of one thing: Corbyn was unelectable. Condescension stood in for a serious understanding of the ideas that made up the Corbyn worldview. But Corbynism's success might have been less surprising were its political content subject to informed scrutiny. Corbynism: A Critical Approach argues that, on closer inspection, Corbynism rests on a way of seeing the world that resonates with broader contemporary political and economic shifts. This resonance confounds claims over electability. In this fascinating book, Matt Bolton and Frederick Harry Pitts explain the Corbyn worldview. Corbyn's platform of economic protectionism at home twinned with problematic affinities abroad rests on a conspiracist understanding of capitalism as a `rigged system' that chimes with, rather than challenges, the populist nativism in an age of Trump and Brexit. Corbyn's mythical image as a paragon of moral exceptionalism underpinned his ascendancy, promoting a form of anti-politics that assesses ideas not by their content or consequences but the identity of those expressing them. The sectarianism and antisemitism associated with elements of the Corbyn movement stem from a truncated critique of capitalism central to Corbynism